Culture of the Slow
IX, 204 p.
Keywords: Across the world, there has been a growing dissatisfaction with the tempo of modern life. Described simply as the 'slow phenomenon', this volume explores this new brand of living that entails not simply slowing down but an embracing of alternative activities that promote meaning, thoughtfulness, engagement and authenticity.